PENGARUH DATA KEUANGAN DAN NON KEUANGAN PADA NILAI PERUSAHAAN (STUDI KASUS PADA STARTUP PATRIAT) - Werthi, Komang Tri; Khrisdayanti, Ni Luh Ayu Cherylinda (Jurnal Bisnis Darmajaya, 2017)
Technological developments influence on technological progress in the world of IT (Information Technology), which is also growing rapidly. This resulted in the company is required to meningkatkatkan its business excellence strategy. This strategy can be achieved either by improving the internal conditions of the company, namely by improving the management strategy, with emphasis on the market for the product, focus, market share and profits, as well as by external expansion. Behind these strategies is most important is how the company determines the value of the company and do business over the companys valuation. There is also information that is not written, namely through the interviews to the directors or officers of the company designated for that activity is corporate secretary. This information is very important because it is the views and projections about the company in the future. The end result of the valuation is a value that is always compared with the price in the market. In addition to commercial enterprises, enterprise IT (Information Technology) or Startup also need minghitung value of the company. Company IT (Information Technology) or pengembangannnya startup companies that are engaged in IT (Information Technology), one of which is Patriarch. Patriarch is a company engaged in the sale of splint shaped puzzle making it easier for medical personnel in the process of supplying and installation. Patriarch in its development requires investment funding from investors. Patriarch need to know the business value of startupnya, so startup Patriarch can easily tell the investor the amount of funds needed at this time.Keywords: Startup, Company Value, Financial, Non-Financial.